2017
DOI: 10.1007/s10909-017-1815-x
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment in Superfluid Neutron-Star Crusts: Hydrodynamic Description and Microscopic Origin

Abstract: In spite of the absence of viscous drag, the neutron superfluid permeating the inner crust of a neutron star cannot flow freely, and is entrained by the nuclear lattice similarly to laboratory superfluid atomic gases in optical lattices. The role of entrainment on the neutron superfluid dynamics is reviewed. For this purpose, a minimal hydrodynamical model of superfluidity in neutron-star crusts is presented. This model relies on a fully four-dimensionally covariant action principle. The equivalence of this fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 101 publications
4
57
0
Order By: Relevance
“…Subsequently, Ho et al (2015Ho et al ( , 2017 show that, by combining a pulsar's glitch activity with a measurement of true age or surface temperature, one can obtain valuable constraints on properties of the superfluid and even measure the mass of the pulsar; for the A g and estimated age of PSR J0537−6910, the pulsar's mass turns out to be much higher than the canonical 1.4M ⊙ . Very recently, Sauls et al (2020) suggest superfluid entrainment may not be as strong as found by Chamel (2012Chamel ( , 2017. More work is needed to resolve the issue.…”
Section: Superfluid and Crust Moment Of Inertia And Pulsar Massmentioning
confidence: 95%
“…Subsequently, Ho et al (2015Ho et al ( , 2017 show that, by combining a pulsar's glitch activity with a measurement of true age or surface temperature, one can obtain valuable constraints on properties of the superfluid and even measure the mass of the pulsar; for the A g and estimated age of PSR J0537−6910, the pulsar's mass turns out to be much higher than the canonical 1.4M ⊙ . Very recently, Sauls et al (2020) suggest superfluid entrainment may not be as strong as found by Chamel (2012Chamel ( , 2017. More work is needed to resolve the issue.…”
Section: Superfluid and Crust Moment Of Inertia And Pulsar Massmentioning
confidence: 95%
“…The hydrodynamic models of entrainment assume that the coherence length of the neutron superfluid is much smaller than other scales in the problem, in particular, the size of the nucleus. On the other hand, band-structure calculations (analogous to those in the theory of solids) predict a strong entrainment, with the density of superfluid neutrons reduced by an order of magnitude [412][413][414]. While these results were obtained in the limit where the pairing can be neglected compared to other scales, specifically the depth of the lattice potential, a semi-analytical model [415] that includes pairing correlations suggests a rather weak entrainment.…”
Section: Collective Modes and Entrainmentmentioning
confidence: 96%
“…Of particular interest for the phenomenology of neutron stars is the hydrodynamical limit, in which case a crustal layer can be considered as a two-fluid system consisting of the unbound neutron superfluid and plasma comprising crustal nuclei and electrons [411][412][413][414][415][416][417][418]. The normal fluid is locked into the motion of the star by the magnetic field.…”
Section: Collective Modes and Entrainmentmentioning
confidence: 99%
“…The neutron superfluid is thus effectively entrained by the crust (see, e.g., Ref. [21] for a recent review). Likewise, neutrons and protons in the core are mutually coupled by nondissipative entrainment effects of the kind originally discussed by Andreev and Bashkin in the context of superfluid 4 He- 3 He mixtures [22]: The mass current ρ q ρ q ρ q of one nucleon species (q = n, p for neutron, proton, respectively) is found to depend on the superfluid velocities V q V q V q of both species, i.e.,…”
Section: Introductionmentioning
confidence: 99%